THE METHODS TO DEVELOP CHILDREN’S SPEECH IN FOREIGN LANGUAGES DURING PRE-SCHOOL EDUCATION - Eshim Mardonov; Nafosat Salimova, (FAN VA TA'LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
The article examines the ways to enhance children’s speech in foreign languages at a young age and suggests possible methods to implement in pre-school education. The authors discuss the challenges and provides relevant solutions and examples.